Transformational Leadership and Artificial Intelligence on Telkom Plaza Performance - Nurnaningsih; Ruslan Abdullah; Ilham Ismail; Asmiati; Andi Yayuk Sri Rahayu (www.amertainstitute.com, 2024)
This study aims to analyze the influence of transformational leadership and artificial intelligence, both partially and simultaneously, on employee performance at Telkom Plaza Parepare. This study uses a quantitative descriptive approach with a data analysis technique in the form of multiple regression, which is carried out with the help of the Statistical Package for the Social Sciences (SPSS) version 26 program. The data used in this study are primary data obtained through questionnaires filled out by respondents. The results of the study indicate that transformational leadership partially does not have a significant effect on employee performance at Telkom Plaza Parepare. Meanwhile, artificial intelligence partially has a significant effect on employee performance at Telkom Plaza Parepare, and both simultaneously also have a significant effect on employee performance.